Impact of Poly-drug and Mono-drug on Aggression and Emotional Dysregulation among Substance Users - Mustafa, Ali Burhan (Journal of Pakistan Psychiatric Society, 2019)
OBJECTIVE: The current study was conducted to measure impact of Poly drug and Mono-Drug on Aggression and Emotional Dysregulation among Substance Users. STUDY DESIGN: cross-sectional research design PLACE AND DURATION OF THE STUDY: This study was conducted in inpatient Department of Psychiatry and Behavioral Sciences Sheikh Zayed Medical College/Hospital, Rahim Yar Khan, from January 2018 to July 2019. SUBJECT AND METHOD: Sample consists of 104 substance users were recruited by using purposive sampling technique. Three scales were administered. Drug addiction scale was used to assess addiction and intensity of the drugs, Buss-perry aggression questionnaire to assess aggression level and difficulties in emotion regulation scale to assess emotional dysregulation of the percipients. Data was entered and analyzed by SPSS 23. REULTS: The current study result revealed that drug addiction has significant and positive impact on aggression (β= 4.89*, p= 0.14) and emotional dysregulation has significant and positive impact on aggression (β= 127.24***, p= .000) among drug users. Furthermore, drug addiction is significantly higher in poly drug users (M= 9.27, t=-3.44**) as compared to mono-drug users (M= 9.27) and overall aggression is also significantly higher in poly drug users (M= 123.83, t= -26***) as compared to mono-drug users (M= 74.85) and difficulty in emotion regulation was also high in poly drug users (M= 12.83, t= -4***) as compared to mono-drug users. Our study has clinical, community and forensic implications. CONCLUSION: The results show the comparison of poly drug (alcohol + opium) and mono drug addiction and its effect on aggression and emotional dysregulation. This study shows that there is higher level Emotion dysregulation and aggression in poly drug users as compare to mono drug. Findings of this study publicized that drug abuse, an accelerating problem in our country; it has negative effects of human behavior. KEYWORDS: Poly-drug; Mono-drug, Aggression; Emotional Dysregulation